THE CONTRIBUTION OF SELF ACCEPTANCE TOWARD HOPELESSNESS OF FEMALE PRISONERS - Pilosusan, Sofia; Afdal, Afdal (Universitas Negeri Padang, 2020)
This study aims to determine the contribution of self acceptance toward hopelessness of female prisoners. The ideal is that female prisoners have good self acceptance so that hopelessness does not occur. However, in reality, there are still many female prisoners who are unable to accept their condition so that they feel that their lives are too heavy to be lived and have no expectations for his future. This research is a descriptive quantitative research. Subjects in this study are female prisoners in LPKA Class IIB Tanjung Pati, Payakumbuh with a total of 32 people. The instrument used in this study was a questionnaire with a Likert scale model. The analysis technique used was a linear regression analysis technique simple and the results show that the value of R2 is 0.152. This means that 15.2% of the contribution of self acceptance towards hopelessness of female prisoners.